Hydrodynamic performance and surface characterisation of antifouling coatings after long-term marine exposure - E. Begovic; G. Assanelli; F. Aiello; A. Amico; A. Amoresano; G. Battaglia; C. Bertorello; L. Bonoldi; M. Bruscagin; F. De Luca; G. Fiori; C. Fontanarosa; et al. (Ocean Engineering, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Lithologies of Dimorphos revealed by boulder morphological classes - F. Tusberti; M. Pajola; L. Penasa; A. Lucchetti; M. Massironi; G. Munaretto; J. Beccarelli; R. Pozzobon; C. Rossi; G. Poggiali; N. Murdoch; C.Q. Robin; et al. (Icarus, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Resolving Symbiodiniaceae Diversity Across Coral Microhabitats and Reef Niches - Wyatt C. Million; Christian R. Voolstra; Gabriela Perna; Giulia Puntin; Katherine Rowe; Maren Ziegler (Environmental Microbiology, 2025)
Dinoflagellates of the family Symbiodiniaceae are important symbionts of diverse marine animals and they also occupy different environmental niches on coral reefs. The link between diversity at ecosystem‐scale to microhabitats of Symbiodiniaceae within the coral holobiont is largely unknown. Using ITS2‐amplicon sequencing, we compared Symbiodiniaceae communities across four environments (seawater, near‐reef vs. distant sediments and turf algae) and two coral microhabitats (tissue, mucus) on a coral reef in the Red Sea. We found that coral and environmental habitats were both dominated by the genera Symbiodinium , Cladocopium and Durusdinium , but environmental habitats additionally harboured Fugacium , Gerakladium and Halluxium . Each environmental habitat harboured a distinct Symbiodiniaceae community. Nonetheless, 17 ITS2 sequences were shared among coral and environmental habitats and were also part of nearly half of the ITS2 type profiles in coral‐based communities. Tissues and mucus of 49 coral colonies from 17 genera had largely identical Symbiodiniaceae communities. Together with the large difference between environmental Symbiodiniaceae communities and those in the coral tissue and mucus, our results indicate a clear barrier between host‐associated and environmental Symbiodiniaceae communities marked by only few shared complete type profiles. Monitoring coral colonies after mucus sampling confirmed its suitability for long‐term monitoring of coral‐associated Symbiodiniaceae communities.

Opaque ventilated façades: Energy performance for different main walls and claddings - O. Roig; S. Summa; C. Pardal; A. Isalgue; C. Di Perna; F. Stazi (Energy and Buildings, 2024)

Liver-on-chip model and application in predictive genotoxicity and mutagenicity of drugs - B. Kopp; A. Khawam; K. Di Perna; D. Lenart; M. Vinette; R. Silva; T.B. Zanoni; C. Rore; G. Guenigault; E. Richardson; T. Kostrzewski; A. Boswell; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Thermal performance of a new low-cost ventilated load bearing masonry with wood-cement blocks - F. Stazi; S. Summa; O. Roig; G. Trozzi; C. Di Perna (Energy and Buildings, 2023)

Flexible thermoelectric energy harvesting system based on polymer composites - T. Rodrigues-Marinho; V. Correia; C.-R. Tubio; A. Ares-Pernas; M.-J. Abad; S. Lanceros-Méndez; P. Costa (Chemical Engineering Journal, 2023)

Experimental and numerical study on a new thermal masonry block by comparison with traditional walls - S. Summa; G. Remia; C. Di Perna; F. Stazi (Energy and Buildings, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Contrasting heat stress response patterns of coral holobionts across the Red Sea suggest distinct mechanisms of thermal tolerance - Christian R. Voolstra; Jacob J. Valenzuela; Serdar Turkarslan; Anny Cárdenas; Benjamin C. C. Hume; Gabriela Perna; Carol Buitrago‐López; Katherine Rowe; Monica V. Orellana; Nitin S. Baliga; Suman Paranjape; Guilhem Banc‐Prandi; et al. (Molecular Ecology, 2021)
Corals from the northern Red Sea, in particular the Gulf of Aqaba (GoA), have exceptionally high bleaching thresholds approaching >5℃ above their maximum monthly mean (MMM) temperatures. These elevated thresholds are thought to be due to historical selection, as corals passed through the warmer Southern Red Sea during recolonization from the Arabian Sea. To test this hypothesis, we determined thermal tolerance thresholds of GoA versus central Red Sea (CRS) Stylophora pistillata corals using multi‐temperature acute thermal stress assays to determine thermal thresholds. Relative thermal thresholds of GoA and CRS corals were indeed similar and exceptionally high (~7℃ above MMM). However, absolute thermal thresholds of CRS corals were on average 3℃ above those of GoA corals. To explore the molecular underpinnings, we determined gene expression and microbiome response of the coral holobiont. Transcriptomic responses differed markedly, with a strong response to the thermal stress in GoA corals and their symbiotic algae versus a remarkably muted response in CRS colonies. Concomitant to this, coral and algal genes showed temperature‐induced expression in GoA corals, while exhibiting fixed high expression (front‐loading) in CRS corals. Bacterial community composition of GoA corals changed dramatically under heat stress, whereas CRS corals displayed stable assemblages. We interpret the response of GoA corals as that of a resilient population approaching a tipping point in contrast to a pattern of consistently elevated thermal resistance in CRS corals that cannot further attune. Such response differences suggest distinct thermal tolerance mechanisms that may affect the response of coral populations to ocean warming.

A placebo-controlled study of the effects of ayahuasca, set and setting on mental health of participants in ayahuasca group retreats - M. V. Uthaug; N. L. Mason; S. W. Toennes; J. T. Reckweg; E. B. de Sousa Fernandes Perna; K. P. C. Kuypers; K. van Oorsouw; J. Riba; J. G. Ramaekers (Psychopharmacology, 2021)
Ayahuasca is a plant concoction containing N,N -dimethyltryptamine (DMT) and certain β-carboline alkaloids from South America. Previous research in naturalistic settings has suggested that ingestion of ayahuasca can improve mental health and well-being; however, these studies were not placebo controlled and did not control for the possibility of expectation bias. This naturalistic observational study was designed to assess whether mental health changes were produced by ayahuasca or by set and setting. Assessments were made pre- and post-ayahuasca sessions in 30 experienced participants of ayahuasca retreats hosted in the Netherlands, Spain, and Germany. Participants consumed ayahuasca ( N = 14) or placebo ( N = 16). Analysis revealed a main effect of time on symptoms of depression, anxiety, and stress. Compared to baseline, symptoms reduced in both groups after the ceremony, independent of treatment. There was a main treatment × time interaction on implicit emotional empathy, indicating that ayahuasca increased emotional empathy to negative stimuli. The current findings suggest that improvements in mental health of participants of ayahuasca ceremonies can be driven by non-pharmacological factors that constitute a placebo response but also by pharmacological factors that are related to the use of ayahuasca. These findings stress the importance of placebo-controlled designs in psychedelic research and the need to further explore the contribution of non-pharmacological factors to the psychedelic experience.

Standardized short‐term acute heat stress assays resolve historical differences in coral thermotolerance across microhabitat reef sites - Christian R. Voolstra; Carol Buitrago‐López; Gabriela Perna; Anny Cárdenas; Benjamin C. C. Hume; Nils Rädecker; Daniel J. Barshis (Global Change Biology, 2020)
Coral bleaching is one of the main drivers of reef degradation. Most corals bleach and suffer mortality at just 1–2°C above their maximum monthly mean temperatures, but some species and genotypes resist or recover better than others. Here, we conducted a series of 18‐hr short‐term acute heat stress assays side‐by‐side with a 21‐day long‐term heat stress experiment to assess the ability of both approaches to resolve coral thermotolerance differences reflective of in situ reef temperature thresholds. Using a suite of physiological parameters (photosynthetic efficiency, coral whitening, chlorophyll a , host protein, algal symbiont counts, and algal type association), we assessed bleaching susceptibility of Stylophora pistillata colonies from the windward/exposed and leeward/protected sites of a nearshore coral reef in the central Red Sea, which had previously shown differential mortality during a natural bleaching event. Photosynthetic efficiency was most indicative of the expected higher thermal tolerance in corals from the protected reef site, denoted by an increased retention of dark‐adapted maximum quantum yields at higher temperatures. These differences were resolved using both experimental setups, as corroborated by a positive linear relationship, not observed for the other parameters. Notably, short‐term acute heat stress assays resolved per‐colony (genotype) differences that may have been masked by acclimation effects in the long‐term experiment. Using our newly developed portable experimental system termed the Coral Bleaching Automated Stress System (CBASS), we thus highlight the potential of mobile, standardized short‐term acute heat stress assays to resolve fine‐scale differences in coral thermotolerance. Accordingly, such a system may be suitable for large‐scale determination and complement existing approaches to identify resilient genotypes/reefs for downstream experimental examination and prioritization of reef sites for conservation/restoration. Development of such a framework is consistent with the recommendations of the National Academy of Sciences and the Reef Restoration and Adaptation Program committees for new intervention and restoration strategies.

Drug liking and wanting, not impulsive action or reflection is increased by 4-fluoroamphetamine - K. P. C. Kuypers; E. B. de Sousa Fernandes Perna; P. C. Dolder; S. W. Toennes; E. L. Theunissen; N. L. Mason; N. R. P. W. Hutten; J. G. Ramaekers (Psychopharmacology, 2018)

Subjective aggression during alcohol and cannabis intoxication before and after aggression exposure - E. B. De Sousa Fernandes Perna; E. L. Theunissen; K. P. C. Kuypers; S. W. Toennes; J. G. Ramaekers (Psychopharmacology, 2016)

Rivastigmine but not vardenafil reverses cannabis-induced impairment of verbal memory in healthy humans - E. L. Theunissen; P. Heckman; E. B. de Sousa Fernandes Perna; K. P. C. Kuypers; A. Sambeth; A. Blokland; J. Prickaerts; S. W. Toennes; J. G. Ramaekers (Psychopharmacology, 2015)

Model investigation about the potential of C band SAR in herbaceous wetlands flood monitoring - F. M. Grings; P. Ferrazzoli; H. Karszenbaum; M. Salvia; P. Kandus; J. C. Jacobo‐Berlles; Pablo Perna (International Journal of Remote Sensing, 2008)

Prostaglandin E2 correlates with histamine production in human colorectal cancer - F. Cianchi; C. Cortesini; F. Perna; V. Fabbroni; C. Uliva; F. Fabrizi; L. Giannini; A. Vannacci; E. Masini (Inflammation Research, 2006)

The effects of eticlopride on Morris water task performance in male and female rats neonatally treated with quinpirole - Russell W. Brown; Kimberly N. Thompson; Ivy A. Click; Razaria A. C. Best; Stephanie K. Thacker; Marla K. Perna (Psychopharmacology, 2005)

Histamine and histidine decarboxylase up-regulation in colorectal cancer: correlation with tumor stage - E. Masini; V. Fabbroni; L. Giannini; A. Vannacci; L. Messerini; F. Perna; C. Cortesini; F. Cianchi (Inflammation Research, 2005)

Isotopic Model (NISOTOP) used to Investigate 15N-Urea Transformations in the Presence of Phenanthrene, Chrysene and Benzo(a)pyrene in a Soil–Plant System - S. Cervelli; F. Di Giovanni; C. Perna; D. Perret (Water, Air, & Soil Pollution, 2000)